Entrepreneurship : Boer Enterprise / Siti Fatimah Mohammed Esa ... [et al.] - Mohammed Esa, Siti Fatimah; Ilias, Sumayah; Yakup, Masniah; Ab. Azid, Asma’ Arina (2007)
Development of business nowadays, more competitive and advance, hence as a first stage, we try to established effective and flexible business that’s namely as BOER ENTERPRISE. BOER ENTERPRISE have four partners. They are Siti Fatimah binti Mohammed Esa, Sumayah binti Ilias, Masniah binti Yakup and Asma’ Arina binti Ab. Azid. We will start our business in January 2008.Our business is located at No 36, Kampung Sri Lukut, Batu 28, 86700 Kahang, Kluang Johor. Basically, the nature of our business is including the product from goat such as goat’s milk, mutton, fertilizer and lamb breed. As mentioned, being business cooperation may face various obstacles and difficulties.